Copper-clad laminate and method for manufacturing the same

A copper-clad laminate with controlled pinhole density and thickness addresses the high defect rate issue in semi-additive processes, enhancing the reliability of flexible printed circuit boards and chip-on-films by reducing pinhole-induced defects.

CN114745849BActive Publication Date: 2024-12-27SUMITOMO METAL MINING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202111181106.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-10-11
Publication Date
2024-12-27
Estimated Expiration
2041-10-11

AI Technical Summary

Technical Problem

Existing copper-clad laminates used in flexible printed circuit boards and chip-on-films suffer from high defect rates due to pinholes in the conductor layer, particularly during the semi-additive process, leading to issues like disconnection and deficiency of fine wiring, especially when forming fine wiring patterns.

Method used

A copper-clad laminate with a conductor layer thickness of 0.4 to 3.0 μm and controlled pinhole density of 0.04/cm², achieved through electrolytic plating using a plating device with rollers having a surface roughness of 0.1 μm or less, to minimize pinhole formation.

Benefits of technology

The method reduces the defect rate of wiring patterns to 30% or less, ensuring high precision and reliability of the formed circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114745849B_ABST
    Figure CN114745849B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a copper-clad laminate and a method for manufacturing the copper-clad laminate, which can reduce the defect rate of a wiring pattern formed by a semi-additive process. The copper-clad laminate (1) of the present invention has a conductor layer (20) containing a copper-plated film (22) formed on the surface of a base film (10). The thickness of the conductor layer (20) is 0.4 to 3.0 μm, and the number of pinholes with a diameter of 5 μm or more is 0.04 / cm 2 A copper-clad laminate (1) having a conductor layer (20) with a thickness of 0.4 to 3.0 μm is obtained by forming a copper-plated film (22) on the surface of a substrate by electrolytic plating while the substrate is conveyed by roller to roller using a plating device. The surface roughness Rmax of all the conveying surfaces of the rollers in the plating device that are in contact with the plating surface of the substrate is 0.1 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper-clad laminate and a method for manufacturing the copper-clad laminate. More specifically, the present invention relates to a copper-clad laminate used for manufacturing a flexible printed wiring board, a chip-on-film, etc., and a method for manufacturing the copper-clad laminate. Background Art

[0002] Flexible printed circuit boards (FPCs) with wiring patterns formed on the surface of resin films and chip-on-films (COFs) with semiconductor chips mounted on flexible printed circuit boards are used in electronic devices such as liquid crystal panels, notebook computers, digital cameras, and mobile phones.

[0003] A flexible printed wiring board is obtained by forming a wiring pattern on a copper-clad laminate by a semi-additive method, a subtractive method, etc. In particular, when fine wiring formation or high-precision wiring dimensions are required, a semi-additive method is used (for example, Patent Document 1).

[0004] In the semi-additive method, the unnecessary part of the conductor layer of the copper-clad laminate is removed by etching. When the conductor layer is too thick, the etching time becomes long, and the wiring part is also etched, so it is difficult for the cross-sectional shape of the wiring to be rectangular. Therefore, the conductor layer of the copper-clad laminate processed by the semi-additive method is preferably a thinner conductor layer. Therefore, as a copper-clad laminate processed by the semi-additive method, a copper-clad laminate having a conductor layer with a thickness of 0.2 to 3.0 μm is often used.

[0005] Chip-on-film is manufactured by sequentially processing copper-clad laminates by wiring pattern manufacturers and component manufacturers. The wiring pattern manufacturer forms a long-strip flexible printed wiring board by arranging a plurality of wiring patterns that will become a plurality of single sheets on a long-strip copper-clad laminate, and sends the flexible printed wiring board to the component manufacturer under the long-strip condition. Here, among the plurality of wiring patterns, wiring patterns with defects such as broken wires and missing wiring are marked with marks indicating defectiveness. The component manufacturer installs semiconductor chips on each wiring pattern. At this time, when the defective rate of the flexible printed wiring board (the proportion of defective wiring patterns among the plurality of wiring patterns formed on the flexible printed wiring board) is high, the productivity of the installation is reduced. Therefore, the flexible printed wiring boards delivered to the component manufacturers mostly specify the allowable defective rate of the wiring pattern. Although the specifications vary depending on the component manufacturer, the allowable defective rate is mostly set at 30%.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2010-108964. Summary of the invention

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a copper-clad laminate and a method for producing the copper-clad laminate, which are capable of reducing the defect rate of a wiring pattern formed by a semi-additive process.

[0010] The copper-clad laminate of the present invention is characterized in that it has a conductor layer containing a copper-plated film formed on the surface of a base film, the thickness of the conductor layer is 0.4 to 3.0 μm, and the number of pinholes with a diameter of 5 μm or more in the conductor layer is 0.04 / cm 2 the following.

[0011] The method for manufacturing a copper-clad laminate of the present invention is characterized in that a copper-clad laminate having a conductor layer with a thickness of 0.4 to 3.0 μm is obtained by using a plating device to form a copper-plated film on the surface of the substrate by electrolytic plating while the substrate is conveyed by rollers. When the copper-clad laminate is obtained using the plating device, the surface roughness Rmax of the conveying surfaces of all rollers in the plating device that are in contact with the plating surface of the substrate is less than 0.1 μm.

[0012] In the copper-clad laminate of the present invention, the number of pinholes with a diameter of 5 μm or more in the conductor layer is set to 0.04 pinholes / cm 2 Hereinafter, the defective rate of the wiring pattern formed by the semi-additive method can be suppressed to 30% or less.

[0013] According to the method for manufacturing a copper-clad laminate of the present invention, a copper-clad laminate having a pinhole diameter of 5 μm or more and a pinhole count of 0.04 / cm 2 The following conductor layers are copper-clad laminates. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a cross-sectional view of a copper-clad laminate according to one embodiment of the present invention.

[0015] Description of Reference Numerals

[0016] 1: copper-clad laminate; 10: base film; 20: conductor layer; 21: metal layer; 21a: base metal layer; 21b: copper thin film layer; 22: copper plating film. DETAILED DESCRIPTION

[0017] Next, embodiments of the present invention will be described based on the drawings.

[0018] (Copper Clad Laminated Board)

[0019] like Figure 1 As shown in FIG. 1 , a copper-clad laminate 1 according to an embodiment of the present invention is composed of a base film 10 and a conductor layer 20 formed on the surface of the base film 10. Figure 1 Although the conductor layer 20 is formed on only one side of the base film 10 , the conductor layer 20 may be formed on both sides of the base film 10 .

[0020] A resin film such as a polyimide film or a liquid crystal polymer (LCP) film can be used as the base film 10. The conductor layer 20 is composed of a metal layer 21 formed by a dry film forming method such as sputtering and a copper-plated film 22 formed by electrolytic plating. The metal layer 21 and the copper-plated film 22 are stacked on the surface of the base film 10 in this order.

[0021] The metal layer 21 is composed of a base metal layer 21a and a copper thin film layer 21b. The base metal layer 21a and the copper thin film layer 21b are stacked in this order on the surface of the base film 10. Usually, the base metal layer 21a is composed of nickel, chromium or a nickel-chromium alloy. The base metal layer 21a may be absent. The copper thin film layer 21b may be formed on the surface of the base film 10 via the base metal layer 21a, or may be formed directly on the surface of the base film 10 without the base metal layer 21a.

[0022] Although not particularly limited, the thickness of the base film 10 is usually 10 to 100 μm. The thickness of the base metal layer 21a is usually 5 to 50 nm, and the thickness of the copper thin film layer 21b is usually 50 to 400 nm. In the case of the copper-clad laminate 1 processed by the semi-additive method, the thickness of the conductor layer 20 is usually 0.4 to 3.0 μm.

[0023] A flexible printed wiring board can be manufactured by processing the copper-clad laminate 1 by a semi-additive method. The flexible printed wiring board is manufactured by the semi-additive method according to the following steps. First, a resist layer is formed on the surface of the copper-plated film 22 of the copper-clad laminate 1. Next, an opening is formed in the portion of the resist layer where the wiring pattern is formed. Next, the copper-plated film 22 exposed from the opening of the resist layer is used as a cathode for electrolytic plating to form a wiring portion. Next, the resist layer is removed, and the conductor layer 20 other than the wiring portion is removed by flash etching or the like. Thus, a flexible printed wiring board is obtained.

[0024] Since the copper-plated film 22 of the copper-clad laminate 1 processed by the semi-additive method is thin, pinholes are easily generated when the copper-plated film 22 is formed by electrolytic plating. In the semi-additive method, copper plating of the wiring pattern is stacked on the copper-plated film 22 by electrolytic plating. At this time, if there are pinholes in the copper-plated film 22, the growth of the stacked copper plating will be hindered, and defects such as disconnection and deficiency of the wiring will occur. In particular, in the case of manufacturing a flip-chip film, since it is necessary to form a fine wiring with a wiring width of less than 15μm, wiring defects caused by pinholes are easily generated.

[0025] The fewer the number of pinholes in the conductor layer 20, the less likely it is that defects will occur in the wiring, thereby reducing the defect rate of the wiring pattern. In the conductor layer 20 of the copper-clad laminate 1 of this embodiment, the number of pinholes with a diameter of 5 μm or more is 0.04 / cm2 As described above, since the number of pinholes in the conductor layer 20 is small, the defect rate of the wiring pattern formed by the semi-additive method can be suppressed to 30% or less.

[0026] (Method for manufacturing copper-clad laminate)

[0027] Next, a method for producing a copper-clad laminate according to one embodiment of the present invention will be described.

[0028] By using a roll-to-roll sputtering device, a metal layer 21 can be formed on the surface of a long strip of base film 10. Hereinafter, an article having a metal layer 21 formed on the surface of the base film 10 is referred to as a substrate. By using a roll-to-roll plating device, a copper-plated film 22 can be formed on the surface of a long strip of base material. Thus, a long strip of copper-clad laminate 1 is obtained.

[0029] The plating device is a device for electrolytically plating a substrate while conveying a long strip of substrate by roller to roller. The plating device has a supply device for delivering the substrate wound into a roll and a winding device for winding the plated substrate (copper-clad laminate 1) into a roll. A pre-treatment tank, a plating tank, and a post-treatment tank are arranged on the conveying path between the supply device and the winding device. Electrolytic plating is performed in the plating tank. While the substrate is conveyed into the plating tank, a copper-plated film 22 is formed on its surface by electrolytic plating.

[0030] The copper plating solution is stored in the plating tank. The copper plating solution contains a water-soluble copper salt. As long as it is a water-soluble copper salt commonly used in copper plating solutions, it can be used without particular limitation. The copper plating solution may contain sulfuric acid. By adjusting the amount of sulfuric acid added, the pH and sulfate ion concentration of the copper plating solution can be adjusted. The copper plating solution may contain additives commonly added to the plating solution. As the additive, one selected from a brightener component, a leveler component, a polymer component, a chlorine component, etc. may be used alone, or two or more may be used in combination.

[0031] The content of each component of the copper plating solution can be arbitrarily selected. However, the copper plating solution preferably contains 15 to 70 g / L of copper and 20 to 250 g / L of sulfuric acid. In this way, the copper plating film 22 can be formed at a sufficient speed. The copper plating solution preferably contains 1 to 50 mg / L of a brightener component. In this way, the precipitated crystals can be miniaturized and the surface of the copper plating film 22 can be smoothed. The copper plating solution preferably contains 1 to 300 mg / L of a leveling agent component. In this way, protrusions can be suppressed and a flat copper plating film 22 can be formed. The copper plating solution preferably contains 10 to 1500 mg / L of a polymer component. In this way, the current can be relaxed to concentrate on the end of the substrate and a uniform copper plating film 22 can be formed. The copper plating solution preferably contains 20 to 80 mg / L of a chlorine component. In this way, abnormal precipitation can be suppressed.

[0032] The temperature of the copper plating solution is preferably 20 to 35° C. In addition, the copper plating solution in the plating tank is preferably stirred. For example, the copper plating solution can be stirred by spraying the copper plating solution ejected from a nozzle onto the substrate.

[0033] The thickness of the copper plating film 22 can be adjusted by the current density and plating time in the electrolytic plating. For example, the thickness of the copper plating film 22 is adjusted so that the thickness of the conductor layer 20 is 0.4 to 3.0 μm.

[0034] The plating device has various rollers for conveying the substrate. Among the rollers of the plating device, as all rollers in contact with the plating surface of the substrate, rollers with a surface roughness (Rmax) of 0.1 μm or less on the conveying surface (the area on the outer peripheral surface of the roller that contacts the plating surface of the substrate) are used. In this way, pinholes are not easily generated when the copper plating film 22 is formed by electrolytic plating. Therefore, it is possible to manufacture a copper plating film with a pinhole diameter of 5 μm or more and a pinhole count of 0.04 / cm 2 The copper-clad laminate 1 includes the following conductor layer 20 .

[0035] Example

[0036] (Common conditions)

[0037] As a base film, a long strip of polyimide film (Upilex, manufactured by Ube Industries, Ltd.) with a width of 570 mm and a thickness of 34 μm was prepared. The base film was set in a magnetron sputtering device. A nickel-chromium alloy target and a copper target were set in the magnetron sputtering device. The composition of the nickel-chromium alloy target was 20% by mass of Cr and 80% by mass of Ni. Under a vacuum environment, a base metal layer composed of a nickel-chromium alloy with a thickness of 25 nm was formed on one side of the base film, and a copper thin film layer with a thickness of 100 nm was formed thereon.

[0038] A copper-plated film is formed on one side of the substrate using a roll-to-roll plating device to obtain a copper-clad laminate. The copper plating solution stored in the plating tank contains 120 g / L of copper sulfate, 70 g / L of sulfuric acid, 16 mg / L of a brightener component, 20 mg / L of a leveler component, 1100 mg / L of a polymer component, and 50 mg / L of a chlorine component. As a brightener component, bis(3-sulfopropyl) disulfide (a reagent manufactured by RASCHIG GmbH) was used. As a leveler component, a diallyldimethylammonium chloride-sulfur dioxide copolymer (manufactured by Nittobo Medical Co., Ltd., PAS-A-5) was used. As a polymer component, a polyethylene glycol-polypropylene glycol copolymer (manufactured by NOF Corporation, Unilube50MB-11) was used. As a chlorine component, hydrochloric acid (35% hydrochloric acid manufactured by Wako Pure Chemical Industries, Ltd.) was used.

[0039] (Example 1)

[0040] Among the rollers provided in the plating apparatus, all rollers that come into contact with the plating surface of the substrate have a conveying surface with a surface roughness (Rmax) of 0.068 to 0.074 μm. The thickness of the copper plating film was adjusted so that the thickness of the conductor layer was 0.4 μm.

[0041] (Example 2)

[0042] Among the rollers provided in the plating apparatus, all rollers that come into contact with the plating surface of the substrate have a conveying surface with a surface roughness (Rmax) of 0.068 to 0.074 μm. The thickness of the copper plating film was adjusted so that the thickness of the conductor layer was 2.0 μm.

[0043] (Example 3)

[0044] Among the rollers provided in the plating apparatus, all rollers that come into contact with the plating surface of the substrate have a conveying surface with a surface roughness (Rmax) of 0.068 to 0.074 μm. The thickness of the copper plating film was adjusted so that the thickness of the conductor layer was 3.0 μm.

[0045] (Comparative Example 1)

[0046] Among the rollers provided in the plating apparatus, all rollers that come into contact with the plating surface of the substrate have a conveying surface with a surface roughness (Rmax) of 4.003 to 4.218 μm. The thickness of the copper plating film was adjusted so that the thickness of the conductor layer was 3.0 μm.

[0047] (Comparative Example 2)

[0048] Among the rollers provided in the plating apparatus, all rollers that come into contact with the plating surface of the substrate have a conveying surface with a surface roughness (Rmax) of 7.101 to 7.129 μm. The thickness of the copper plating film was adjusted so that the thickness of the conductor layer was 0.5 μm.

[0049] Samples of 250×160 mm were cut out from each copper-clad laminate obtained in Examples 1 to 3 and Comparative Examples 1 and 2. Each sample was inspected using backlighting with a halogen lamp as the light source, and the number of pinholes with a diameter of 5 μm or more was counted. Visual inspection was performed while comparing with a sample with a pinhole of 5 μm prepared in advance. The results are shown in Table 1.

[0050] In Examples 1 to 3 using a roller having a surface roughness (Rmax) of 0.068 to 0.074 μm, the number of pinholes was 0.04 / cm. 2 On the other hand, in Comparative Examples 1 and 2 using rollers having a surface roughness (Rmax) of 4.003 to 4.218 μm or 7.101 to 7.129 μm, the number of pinholes exceeded 0.04 / cm.2 Thus, it was confirmed that when a roller with a surface roughness (Rmax) of 0.1 μm or less was used, 0.04 pinholes / cm2 with a diameter of 5 μm or more could be produced. 2 The following conductor layers are copper-clad laminates.

[0051] Next, each copper-clad laminate obtained in Examples 1 to 3 and Comparative Examples 1 and 2 is processed to manufacture a flexible printed wiring board. The flexible printed wiring board is manufactured according to the following steps. A dry film resist is laminated on the surface of the copper-plated film of the copper-clad laminate to form a resist mask in which a plurality of wiring patterns are arranged. The size of each wiring pattern is approximately 70×40 mm, the minimum pitch is 20 μm, and the wiring width is 10 μm. Next, the copper-plated film exposed from the opening of the resist mask is electrolytically plated as a cathode, and the copper plating is laminated so that the total thickness thereof and the conductor layer of the copper-clad laminate is 8 μm.

[0052] The laminated copper plating (wiring pattern) exposed from the opening of the resist mask was observed under a microscope. A wiring pattern with a defect or disconnection of more than one-third of the wiring width was judged as defective, and the defective rate of the wiring pattern was calculated. The results are shown in Table 1.

[0053] The number of pinholes in the conductor layer was confirmed to be 0.04 / cm 2 In the following Examples 1 to 3, the defective rate was 30% or less, which was within the allowable range. In contrast, the number of pinholes in the conductor layer was 0.07 pinholes / cm 2 , 0.10pcs / cm 2 In Comparative Examples 1 and 2, the defective rate exceeded 30%. Therefore, it was confirmed that when the number of pinholes in the conductor layer was 0.04 / cm 2 When the defect rate of the wiring pattern formed by the semi-additive method is less than 30%, the defect rate of the wiring pattern formed by the semi-additive method is less than 30%.

[0054] In addition, it can be seen from Table 1 that the fewer the number of pinholes in the conductor layer, the lower the defect rate of the wiring pattern. 2 When the number of pinholes is 0.02 / cm 2 When the number of pinholes is 0.01 / cm 2 When the defect rate is less than 10%, the defect rate can be less than 18%.

[0055] [Table 1]

[0056]

Claims

1. A copper-clad laminate, characterized in that: The copper-clad laminate has a conductor layer including a copper-plated film formed on the surface of a base film. The thickness of the conductor layer is 0.4 to 3.0 μm, and the number of pinholes with a diameter of 5 μm or more in the conductor layer is 0.01 / cm 2 the following, The conductor layer is composed of a metal layer formed on the base film by a dry film forming method and a copper plating film formed on the metal layer by electrolytic plating.

2. A method for manufacturing a copper-clad laminate, characterized in that: A metal layer is formed on the surface of a long strip-shaped base film using a roll-to-roll sputtering device to form a substrate, and a copper-plated film is formed on the surface of the substrate by electrolytic plating while the substrate is conveyed by roll-to-roll using a plating device to obtain a pinhole having a thickness of 0.4 to 3.0 μm and a diameter of 5 μm or more with a number of 0.01 pinholes / cm 2 The following conductor layers are copper-clad laminates. When a copper-clad laminate is obtained using a plating apparatus, the surface roughness Rmax of all conveying surfaces of rollers in the plating apparatus that are in contact with the plating surface of the substrate is 0.1 μm or less.

Citation Information

Patent Citations

  • Method for manufacturing circuit board

    JP2010108964A

  • Method for manufacturing plated film, cathode roll for plating, and method for manufacturing circuit board

    CN1675411A

  • Method for manufacturing metal resin composite film, metal resin composite film and its use

    JP2005264303A

  • Flexible copper-clad laminate and flexible copper clad laminate with carrier

    JP2008087254A

  • Copper foil with release film

    JP2015104891A